POWERS OF THE PRESIDENT OF THE REPUBLIC IN THE LEGISLATIVE PROCESS - Šinkūnas, Haroldas; Svetikaitė, Rasa (Teisė, 2017)
In this article the constitutional powers of the President of the Republic in the legislative process, while acting as a counterweight to the legislature are analyzed: the right of legislative initiative, the promulgation of laws adopted by a referendum and the Seimas and the return of laws passed by the Seimas to the Seimas for reconsideration, as well as the appeal to the Constitutional Court as an influential mean on the legislative process.